Ultra-Short Antimicrobial Peptoids Show Propensity for Membrane Activity Against Multi-Drug Resistant Mycobacterium tuberculosis - Khara, Jasmeet Singh; Mojsoska, Biljana; Mukherjee, Devika; Langford, Paul R.; Robertson, Brian D.; Jenssen, Håvard; Ee, Pui Lai Rachel; Newton, Sandra M. (Frontiers in Microbiology, 2020)
Tuberculosis (TB) results in both morbidity and mortality on a global scale. With drug resistance on the increase, there is an urgent need to develop novel anti-mycobacterials. Thus, we assessed the anti-mycobacterial potency of three novel synthetic peptoids against drug-susceptible and multi-drug resistant (MDR) Mycobacterium tuberculosis in vitro using Minimum Inhibitory Concentration, killing efficacy and intracellular growth inhibition assays, and in vivo against mycobacteria infected BALB/c mice. In addition, we verified cell selectivity using mammalian cells to assess peptoid toxicity. The mechanism of action was determined using flow cytometric analysis, and microfluidic live-cell imaging with time-lapse microscopy and uptake of propidium iodide. Peptoid BM 2 demonstrated anti-mycobacterial activity against both drug sensitive and MDR M. tuberculosis together with an acceptable toxicity profile that showed selectivity between bacterial and mammalian membranes. The peptoid was able to efficiently kill the bacteria both in vitro and intracellularly in murine RAW 264.7 macrophages, and significantly reduced bacterial load in the lungs of infected mice. Flow cytometric and time lapse fluorescence microscopy indicate mycobacterial membrane damage as the likely mechanism of action. These data demonstrate that peptoids are a novel class of antimicrobial which warrant further investigation and development as therapeutics against TB.